EKOSUFISME SEBAGAI PRINSIP KEWARGANEGARAAN GLOBAL DALAM MENGHADAPI PERUBAHAN IKLIM - Anggara, Jefry; Nurwahidin, Nurwahidin; Muttaqin, Mohammad Izdiyan (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract: Climate change is a global challenge that requires collective engagement from around the world. This research formulates that Hossein Nasr's ecosufism can be applied as a principle of global citizenship and plays a role in overcoming the challenges of climate change. Using a descriptive qualitative method with library research and using an interdisciplinary approach because it combines several scientific fields, including ecology, Sufism, global citizenship education, and other sciences. Ecosufism views environmental sustainability as an integral part of spiritual understanding and humanity. Sufistic communities in Indonesia have implemented ecosufism in their practices, such as planting trees, using renewable energy, and reducing waste. The principles of ecosufism can be considered as principles of global citizenship in the sense that it emphasizes global awareness, responsibility and action in preserving and protecting the environment and addressing the challenges of climate change. If integrated with global citizenship education, ecosufism can help individuals develop a sustainable global perspective and promote more effective global citizenship. Ecosufism offers a holistic solution to the global challenges faced by society today. By integrating Sufistic values and the principles of global citizenship education, ecosufism can be a driving force in efforts to address climate change. Keywords: Ecosufism, Global Citizenship, Climate Change, Sufism, Hossein Nasr